Characterization of the electrical properties of an optical device manufactured with CMOS 0.35 μm technology - Ricardo Yauri; Vanessa Gamero; Marco Alayo (Institute of Advanced Engineering and Science, 2023)
Currently, the relevance of optical devices has increased due to the physical limitations of the electrical transmission medium and the proximity of the limit of Moore's Law. Furthermore, the fabrication of optical devices on monolithic silicon substrates has gained importance in recent years thanks to manufacturing technologies in the microelectronics industry. For this reason, this paper aims to carry out the electrical characterization of an optical device manufactured with commercial austria micro syste m technology of complementary metal oxide semiconductors of 0.35 μm. The methodology consists of implementing an optical device, with an incandescent optical source called a microlamp, a waveguide and a photodiode. The microlamp was projected between two m etal layers connected by tungsten vias that act as filaments covered by SiO 2 dielectric to prevent oxidation. The results of the electrical characterization of the optical device show that the microlamp reaches a maximum current of 48 mA and stops working at higher currents. The waveguide was designed with a SiO 2 core and it was discovered that the TiN layers were found to be part of the waveguide causing it to behave as an emitter in the 2.5 - 5 µm region.